ILTER – The International Long-Term Ecological Research Network as a Platform for Global Coastal and Ocean Observation - Muelbert, José H.; Nidzieko, Nicholas J.; Acosta, Alicia T. R.; Beaulieu, Stace E.; Bernardino, Angelo F.; Boikova, Elmira; Bornman, Thomas G.; Cataletto, Bruno; Deneudt, Klaas; Eliason, Erika; Kraberg, Alexandra; Nakaoka, Masahiro; et al. (Frontiers in Marine Science, 2019)
Understanding the threats to global biodiversity and ecosystem services posed by human impacts on coastal and marine environments requires the establishment and maintenance of ecological observatories that integrate the biological, physical, geological and biogeochemical aspects of ecosystems. This is crucial to provide scientists and stakeholders with the support and knowledge necessary to quantify environmental change and its impact on the sustainable use of the seas and coasts. In this paper, we explore the potential for the coastal and marine components of the International Long-Term Ecological Research Network (ILTER) to fill this need for integrated global observation, and highlight how ecological observations are necessary to address the challenges posed by climate change and evolving human needs and stressors within the coastal zone. The ILTER is a global network encompassing 44 countries and 700 research sites in a variety of ecosystems across the planet, more than 100 of which are located in coastal and marine environments (ILTER-CMS). While most (50%) of the ILTER-CMS were established after the year 2000, in some cases they date back to the early 1900s. At ILTER sites a broad variety of abiotic and biotic variables are measured, which may feed into other global initiatives. The ILTER community has produced tools to harmonize and compare measurements and methods, allowing for data integration workflows and analyses between and within individual ILTER sites. After a brief historical overview of ILTER, with emphasis on the marine component, we analyze the potential contribution of the ILTER-CMS to global coastal and ocean observation, adopting the “Strength, Weakness, Opportunity and Threats (SWOT)” approach. We also identify ways in which the in situ parameters collected at ILTER sites currently fit within the Essential Ocean Variables framework (as proposed by the Framework for Ocean Observation recommendations) and provide insights on the use of new technology in long-term studies. Final recommendations point at the need to further develop observational activities at LTER sites and improve coordination among them and with external related initiatives in order to maximise their exploitation and address present and future challenges in ocean observations.